Valorisation of Lignin into Value-added Materials - Kamara, Ibrahim (My University, 2021)
About 50 – 70 million tons of lignin is produced annually; however, only 1- 2 % of this is used in the production of value-added products (concrete additive, dispersant, animal feed, resins and adhesives and vanillin production).[1,2] The valorisation of lignin has been limited mainly because of its structural complexity and challenges in finding a green, robust, and cost-effective solvents.[3–5] Nonetheless, lignin is gaining interest in the development of value added products due to its low cost, renewability, biodegradability, nontoxicity, high carbon content, and high thermal stability.[5] The presence of different functional groups in lignin makes it a suitable material that can be fine-tuned through modification. Several studies have shown that lignin can be chemically modified to make films and coatings with enhanced hydrophobic properties which can be prospectively used for a variety of practical applications (self-cleaning, antibacterial, oil-water separation, corrosion resistance, etc.).[6–8] In this study, we explored the synthesis of different Kraft lignin (KL) derivatives and their potential application as hydrophobic/superhydrophobic coatings. Kraft lignin was successfully modified by esterification and silylation using common synthetic methods. The thermal properties of the derived materials were evaluated using thermo gravimetric analysis (TGA). The thermal stability generally decreases with increase in degree of substitution. However, fluorinated-KL esters and silylated-KL have shown enhanced thermal stability. Thus, fluorination and silylation proved to be viable methods to improve the thermal stability of KLs. All modified samples were soluble in the constituent solvents used for their synthesis. This facilitated the dissolution and the subsequent spin-coating of films on glass slide, polyethylene terephthalate (PET) film, and filter paper. Atomic force microscopy (AFM) studies confirmed the formation of uniform and continuous films for most of the derivatives on those surfaces. Water contact angle (WCA) measurements revealed that hydrophobic properties of esters generally increased with an increase in carbon chain length. Lignin esters had water contact angle as high as 134±9° with fluoroalkyl esters exhibiting higher thermal stability. Furthermore, silylated KL showed better hydrophobic and thermal properties compared to esters. Scanning electron microscopy (SEM) images showed the considerable change in structure of KL induced by the chemical modification with silanes which consequently resulted in water contact angles of up to 160° for KL silylated samples. This work showed that using relatively simple chemical modification process, Kraft lignin can be modified into derivatives with superhydrophobic properties which with further research can be potentially employed in replacing fossil fuel-based materials in various industrial applications.
Keywords: Kraft lignin, esterification, silylation, film, coating, hydrophobicity, water contact angle